Phenomenology or deconstruction? the question of ontology in Maurice Merleau-Ponty, Paul Ricur and Jean-Luc Nancy - Watkin, David 1941-2018 (Edinburgh University Press, 2009)
Phenomenology or Deconstruction? challenges traditional understandings of the relationship between phenomenology and deconstruction through new readings of the work of Maurice Merleau-Ponty Paul Ricoeur and Jean-Luc Nancy